First record of the genus Ctenipocoris (Heteroptera: Naucoridae) in Central America, with a preliminary key to the American species and description of a new species - Herrera, Federico (Zootaxa, 2013)
A new naucorid species, Ctenipocoris oscari Herrera NEW SPECIES, is herein described for Costa Rica. It is the first species to be described in Central America and the sixth American species. Comparative notes are provided to differentiate this species from the others. Type material is deposited at the Zoological Museum of the University of Costa Rica (MZUCR), San José, Costa Rica. A preliminary key to the American species of the genus is provided.